2015
DOI: 10.1039/c5ta00094g
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Mn co-loaded hierarchically porous zeolite beta: a highly efficient synergetic catalyst for soot oxidation

Abstract: A hierarchically porous zeolite beta as a carrier was made by surfactant-assisted hydrothermal treatment and subsequent alkali etching, and the Cu/Mn species were co-loaded into the carrier. The obtained catalyst exhibits excellent catalytic activity and water-resistance for soot catalytic oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 35 publications
4
25
0
Order By: Relevance
“…It is found that the mBeta possesses a rough surface morphology with diameter about 200-400 nm, suggesting the generation of the mesoporous structure. 16 Aer loading with Fe and Pt species, no obvious aggregates could be found ( Fig. 2b and c), further indicating that Fe and Pt species are highly dispersed onto/into the zeolite support, consistent with the XRD results.…”
Section: Structural and Morphology Characteristicssupporting
confidence: 84%
See 1 more Smart Citation
“…It is found that the mBeta possesses a rough surface morphology with diameter about 200-400 nm, suggesting the generation of the mesoporous structure. 16 Aer loading with Fe and Pt species, no obvious aggregates could be found ( Fig. 2b and c), further indicating that Fe and Pt species are highly dispersed onto/into the zeolite support, consistent with the XRD results.…”
Section: Structural and Morphology Characteristicssupporting
confidence: 84%
“…Recently, mesoporous zeolites as the catalyst support have received much attention owing to the high surface area, high adsorption capacity, and excellent hydrothermal stability. 16 Moreover, the doping of heteroatoms Al + in the [SiO 4 ] makes zeolite have rich acidic sites and a larger number of oxygen vacancies, which is helpful to the adsorption of oxygen. 17 Therefore, it is promising to construct a kind of noble metal and Fe species co-loaded mesoporous zeolite as a highly-efficient catalyst for the CO oxidation by reasonably modulating the pore structure and active species.…”
Section: Introductionmentioning
confidence: 99%
“…Following aw ell-accepted procedure: [33] carbon black from Degussa (1 = 10-50 nm) was chosen as the model soot, then soot (10 mg) and catalyst (100 mg) were mixed thoroughly for 20 min with as patula to simulate the loose contact mode, which is more representative of the real contact conditions. [28] Next, silica pellets (1 g) were added and mixed using as patula for 10 min to avoid a pressure drop and favor heat transfer.…”
Section: Activitytestingmentioning
confidence: 99%
“…Copper-manganese oxides have been studied thoroughly and demonstrated to be highly active for various reactions, [29][30][31][32][33] which include soot combustion. [33] Excellent activity towardss oot catalytic combustion has already been achieved on the copper-manganese oxide catalyst (CuMnO) prepared by am odifiedc oprecipitationm ethod developedi no ur previous work. [34] Herein, furtherK NO 3 -modification was introduced into the production of CuMnOt or esult in aK -modified catalyst CuMnO(K), and ad ecreasing of the T f value to 338 from 360 8C was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Soot oxidation is a typical heterogeneous catalytic reaction containing solid particles as reactant. The type of soot‐catalyst contact is one of the crucial factors that influence the catalytic activity of a catalyst on soot combustion . Tight contact could be the appropriate one to achieve good activities which is obviously due to increase contact points between catalyst and soot particulates.…”
Section: Catalytic Activity Studiesmentioning
confidence: 99%